Role of Strategic Flexibility in Enhancing Innovation Performance From a Futuristic Perspective - Hazhar Omer Mohammed; Zana Majed Sadq; Nabaz Nawzad Abdullah; Hawkar Rashid Arab (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
When organizations attempt to produce on-demand products and consider customers’ expectations, the organization’s environment changes. In this regard, the organizations have a robust understanding of the possible changes, whether internal or external, and consider a wide range of policies. The organization must identify all significant changes occurring inside and outside the organizational structure. Therefore, strategic flexibility is related to the organization’s capacity to identify the external changes or the changes that have quickly happened in the external environment. This study attempts to identify whether changes from the external environment genuinely enhance organizational innovation. The findings of this study indicated that such kinds of dramatic changes strengthen organizations as it assists in knowing strategic competitors. The study asserts that innovation of various forms occurs in different ways, but as a general topic, the activity of innovation is mainly related to outgrown to the other business or the suspected firms which might have been going through the same kinds of economic condition. The study found that organizations use flexible production policies to maintain their competitive advantage in the competitive labour market. The study highlights that flexibility is the most essential tool for organizations to survive, especially when competing businesses in the same industry with the same size.